FRI0460 Pulmonary Fibrosis in Anca-Associated Vasculitis: Clinical Characteristics and Long-Term Followup of 49 Patients. (10th June 2014) - Comarmond, C.; Crestani, B.; Tazi, A.; Hervier, B.; Adam Marchand, S.; Nunes, H.; Cohen-Aubart, F.; Wislez, M.; Cadranel, J.; Housset, B.; Lloret-Linares, C.; Sève, P.; et al.
Abstract : Background: Pulmonary fibrosis (PF) is a rare manifestation observed in patients with antineutrophil cytoplasmic antibodies (ANCA)-associated vasculitis (AAV), particularly microscopic polyangiitis (MPA). Objectives: To report long-term outcome of a cohort of patients with the uncommon association of PF and AAV. Methods: We performed a retrospective multicentric study of characteristics and outcome of patients with PF associated to AAV, fulfilling the ACR and/or Chapel Hill definitions. Results: Forty nine patients [30 (61%) men, median age at diagnosis of AAV of 68 [58–73] years] with PF associated to AAV were identified. Forty (81.6%) patients had microscopic polyangiitis and 9 (18.4%) had granulomatosis with polyangiitis. The diagnosis of PF preceded the onset of vasculitis in 22 (45%) patients. Usual interstitial pneumonia was the main radiological pattern (n=18, 43%). ANCA were mostly of anti-myeloperoxydase specificity (88%). All patients were treated with steroids as induction therapy, combined with cyclophosphamide (CYC) (n=36, 73.5%) or rituximab (RTX) (n=1, 2%). Factors associated with mortality included occurrence of chronic respiratory insufficiency (HR 7.44, 95% CI (1.6 to 34.5), P=0.003), older age at PF diagnosis (HR 1.08, (1.02-1.13), P=0.005), and a higher eosinophil count at AAV diagnosis (HR 1.32, (1.07-1.63), P=0.0084). The 3-year survival rate in patients treated with steroids alone or combined with immunosuppressant (CYC or RTX) as induction therapy was of 64% (95% CI, 41-99) and 94% (95% CI, 86-100), respectively ( P =0.03, Fig. 1 ). After a median follow-up of 48 [14–88] months, eighteen (37%) patients died, including 11 related to respiratory insufficiency. Conclusions: PF is a rare manifestation of AAV with a very poor prognosis. Induction therapy with CYC might improve the outcome. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4159